The BiteBarrier transfluthrin emanator demonstrates significant protection against susceptible and resistant malaria and arbovirus vectors in semi-field trials in Tanzania - Masudi Suleiman Maasayi; Johnson Kyeba Swai; Joseph Barnabas Muganga; Jason Moore; Jennifer Claire Stevenson; Michael Coleman; Neil Francis Lobo; Sarah Jane Moore; Mgeni Mohamed Tambwe (PLoS ONE, 2025)
Controlling mosquito-borne diseases is becoming increasingly challenging due to factors such as insecticide resistance and shifts in mosquito behavior. The increasing proportion of early evening, morning, and outdoor biting reduces the effectiveness of core interventions like bed nets, which mainly protect people while sleeping indoors. In response, spatial emanators that release volatile active ingredients into the surrounding air to reduce human-vector contact offer a scalable, complementary strategy. This study evaluated the impact of BiteBarrier, a transfluthrin-based spatial emanator, over eight weeks of aging against multiple mosquito species in a semi-field system simulating both indoor and outdoor settings. We assessed the protective efficacy using both landing rate and feeding success methods across five mosquito species, including pyrethroid susceptible Anopheles gambiae sensu stricto (s.s.) and Aedes aegypti; An. gambiae s.s. with knock down resistance (KDR); and pyrethroid resistant An. funestus and Culex quinquefasciatus with upregulation of mixed function oxidases. The results show that the feeding endpoint provides more robust estimates of protective efficacy compared to the landing endpoint. The BiteBarrier provided over 93% (95% CI: 92–93) protection indoors and 80% (95% CI: 78–81) outdoors against mosquito bites and substantial mortality 47% (95% CI: 43–53) indoor and 26% (95% CI: 22–30) outdoors, regardless of mosquito species or resistance status. Overall, the BiteBarrier shows potential as a tool for reducing mosquito bites and vectorial capacity, offering protection over at least eight weeks of use for both indoor and outdoor environments.